Exploring Scaffolded Assessment in Research-Based Project Classes: A Qualitative Perspective on Student and Lecturer Experiences - Santosa, Imam; Fadli, Muhammad Rijal; Sadikin, Irma Savitri; Iskandar, Ifan; Jonuzi, Vjollca (Universitas Pendidikan Mandalika, 2025)
This study investigates the benefits and challenges of implementing scaffolding strategies in research-based project classes at Esa Unggul University. The participants consisted of 37 undergraduate students enrolled in a research class focused on producing academic research articles. Using a qualitative case study approach, data were collected through semi-structured interviews and analyzed using thematic analysis to explore students' experiences with scaffolding throughout the research project process. The findings revealed that scaffolding enhanced students' critical thinking, time management, academic motivation, and ability to use feedback effectively. Structured support mechanisms—such as critical questioning, phased assignments, and staged feedback—enabled students to engage more deeply with complex research tasks and fostered the development of independent learning skills. However, several challenges emerged, including high cognitive load, unclear scaffolding instructions, difficulty applying feedback, and student overreliance on lecturer guidance. These results suggest that while scaffolding is a powerful instructional strategy, its effectiveness depends on intentional, flexible, and well-sequenced design that supports both structure and autonomy. This study contributes to instructional design by offering practical insights into how scaffolding can be optimized to meet the diverse needs of learners in higher education research setting.